Improve Students’ Learning Experience in General Chemistry Laboratory Courses - Sheng, Yinghong; Zhao, Fan (HCI in Games: Serious and Immersive Games, 2021)
The current shift from a traditional classroom laboratory to a partial remote virtual lab is mainly due to COVID-19 pandemic. This pedagogical change is forcing academic institutions to rethink and redesign their lab courses. VR is promising technology to support this change. This study reviews current literature of the VR systems applied in higher education, clarifies some technical terms related to VR technology, and identifies the strengths and weaknesses of this technology. After a semi-interview with faculty members and students in the Chemistry department at a US university, we propose a new hybrid lab design with VR technology based on the literature review and interview results.